2016
DOI: 10.1111/jfbc.12262
|View full text |Cite
|
Sign up to set email alerts
|

Assessment the Protective Role of Quercetin on Acrylamide-Induced Oxidative Stress in Rats

Abstract: This study aimed to elucidate whether quercetin treatment could modulate acrylamide (ACR)‐induced DNA damage and oxidative changes in rat brain, liver, kidneys and testes tissues. Fifty adult albino rats were divided into five groups. The first group served as normal control, second group received 50 mg/kg quercetin (QTN) and third group received 20 mg/kg ACR. Fourth and fifth groups received dose of ACR along with 25 or 50 mg/kg QTN, respectively. ACR and QTN were given by oral administrations for 30 days. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 54 publications
(81 reference statements)
5
18
0
Order By: Relevance
“…Low dose therapeutic group showed intestinal villus rupture. Two high dose groups showed slight intestinal villus rupture the collapse of the antioxidant system in rats, which is manifested by a sharp decrease in antioxidant enzyme (SOD, CAT) activity and the level of antioxidant (GSH) [28][29][30]. At this time, excessive ROS continuously attacked the cells, and the accumulation of lipid peroxides in the cells eventually caused oxidative damage to various tissues of the rats [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Low dose therapeutic group showed intestinal villus rupture. Two high dose groups showed slight intestinal villus rupture the collapse of the antioxidant system in rats, which is manifested by a sharp decrease in antioxidant enzyme (SOD, CAT) activity and the level of antioxidant (GSH) [28][29][30]. At this time, excessive ROS continuously attacked the cells, and the accumulation of lipid peroxides in the cells eventually caused oxidative damage to various tissues of the rats [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicate the preventive effect of quercetin towards ACR exposure. El-Beltagi et al (68) showed that oral administration of ACR induced elevation of inflammatory markers and oxidative stress parameters in rats, and coadministration of quercetin in dose 25 and 50 mg/kg ameliorated these unfavorable effects, which suggests that quercetin has a protective role in ACR-induced oxidative stress in the animal model. Yang et al (69) also indicated that quercetin had a beneficial effect on the metabolic profile of the serum of ACR-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin enhanced DA and serotonin levels, reduced biomarkers of oxidative stress, restored acetylcholinesterase (AChE) activity in ACR-treated rats. It can move across the BBB and exhibit its therapeutic efficiency [36,68,69]. Other compounds like metformin, minocycline and zolpidem also show similar therapeutic effects to dietary supplements when administered to ACR-treated rats [70][71][72] (Table 2).…”
Section: Phytochemicalsmentioning
confidence: 99%